2016
DOI: 10.21548/32-1-1365
|View full text |Cite
|
Sign up to set email alerts
|

Colour Evolution of Rosé Wines after Bottling

Abstract: This research reports on the colour evolution of six rosé wines during sixteen months of storage in the bottle. Colour changes were determined in terms of CIELAB colour parameters and in terms of the common colour categories used in visual assessment. The colour measurement method reproduces the visual assessment conditions during wine tasting with respect to wine sampler, illuminating source, observing background and sample-observer geometry. CIELAB L*, a*, b*, C* and h ab colour coordinates were determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Al realizar el cálculo de la diferencia de color presentada (ΔE*) donde, T1-T2 reflejaron una pequeña diferencia (0,554) y T2-T3 con ΔE* 0,903 y T1-T3 con un ΔE* 1,064 llegando a duplicar su diferencia de color pero aun así no llega a ser evidente, lo que demuestra que aunque existan cambios de color en función del empaque, ésta es difícilmente apreciable Las medias con la misma letra en las filas no difieren estadísticamente entre sí, prueba de LSD Fisher (P < 0,05). por el consumidor debido a que el umbral apenas perceptible a la vista es desde ΔE*= 2,3±1,3 [20].…”
Section: Resultsunclassified
“…Al realizar el cálculo de la diferencia de color presentada (ΔE*) donde, T1-T2 reflejaron una pequeña diferencia (0,554) y T2-T3 con ΔE* 0,903 y T1-T3 con un ΔE* 1,064 llegando a duplicar su diferencia de color pero aun así no llega a ser evidente, lo que demuestra que aunque existan cambios de color en función del empaque, ésta es difícilmente apreciable Las medias con la misma letra en las filas no difieren estadísticamente entre sí, prueba de LSD Fisher (P < 0,05). por el consumidor debido a que el umbral apenas perceptible a la vista es desde ΔE*= 2,3±1,3 [20].…”
Section: Resultsunclassified
“…Versari et al (2008) state that it is difficult to correlate the relationship between wine colour and its chemical composition. Hernández et al (2011) also found that there is a general lack of agreement about absorbance measurements and visual colour assessment. This explains why the panellists only start noticing the pink colour change at 0.03 AU.…”
Section: Ranking the Point Of Pinking Perceptionmentioning
confidence: 99%
“…The rosé wine collection exhibited large color differences from almost white to light red, covering the entire range of shades described in the Color Chart from the Centre du Rose ® (Centre Du Rosé.fr., available online: https://centredurose.fr/nuanciers-vins-roses, accessed 30 January 2022). It should be emphasized that there is no definition of rosé wine based on color and examination of color values reported in the literature for red and rosé wines show large variations and overlapping (e.g., L*: 28-70, a*: 28-52, b: 8-36 in reds [18]; L*: 38-45; a*: 48-52; b*: 24-28 in rosés [15]). However, much lighter colors have been reported in other studies (L*: 79-86, a*: 17-25, b*: 8-9 [16]; L*: 92-95, a*: 2-5, b*: 7-11 [11]) and the light "salmon" shade, which is characteristic of Provence wines, is generally the leader on the global market although consumer preferences may vary between regions [1].…”
Section: Rosé Wine(s) Versus Red Winementioning
confidence: 99%
“…Changes in color [15] and/or phenolic composition [11,16] of rosé wines induced by wine processing and storage have also been described but the relationships between phenolic composition and color are only partly understood. The objective of the present work was to explore the phenolic composition of rosé wines and explain differences in color styles.…”
Section: Introductionmentioning
confidence: 99%